ANALISIS KETERAMPILAN BAHASA PADA SISWA DALAM PEMBELAJARAN MATEMATIKA - Siti Napfiah; K, Anggi Widiarti (Universitas Islam Raden Rahmat Malang, 2023)
Analysis of Language Skills in Students Mathematics Learning. This study aims to answer the results of the analysis of language skills in someone in the process of learning mathematics. The research method used in this research is a qualitative method. In the process of this research, researchers used descriptive data analysis. Data collection is done by observation and interviews. The data taken came from class III students at SD Negeri Pujon Kidul. The analysis of the data obtained was processed into three stages, namely data reduction, data presentation, and drawing conclusions from the data obtained. The research results obtained showed that the language skills of class III students at Pujon Kidul Public Elementary School in learning mathematics. Based on this research language skills acquired include 58% listening ability, 70% speaking ability, 82% reading ability, and 72% writing ability. The relationship between language and mathematics is needed for mathematical communication. So learning mathematics can be easier if you have good language skills. When improving language skills, it is necessary to apply the image method as a supporting tool in teaching and learning activities to improve the quality of language skills in students.